A Neoclassical Model of the Dual Economy with Capital Accumulation in Agriculture - Amano, M. (Review of Economic Studies, 1980)
Journal Article A Neoclassical Model of the Dual Economy with Capital Accumulation in Agriculture Get access Masanori Amano Masanori Amano University of Tsukuba Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 5, October 1980, Pages 933–944, https://doi.org/10.2307/2296923 Published: 01 October 1980 Article history Received: 01 January 1979 Accepted: 01 February 1980 Published: 01 October 1980